The relational mediation approach through the lens of intersubjectivity: The promises and limits - Dupuis, Natalie (Université d'Ottawa | University of Ottawa, 2026)
This thesis endeavours to make a critical assessment of the relational mediation approach and discerns gaps that remain insufficiently accounted for in the models selected. Accounting for these gaps and how they impact relational mediation processes creates opportunities to improve and further develop relational mediation theories. Further development in the theory may thus equip mediators with additional aptitudes for assessing how they can best assist parties with unique needs and help to determine if the conditions for mediation are propitious for success. Using an interdisciplinary approach to understanding relational mediation practice, this thesis develops a view of relational mediation models as distinctly phenomenological in orientation with the ultimate goal being the emergence of a new intersubjective understanding between parties in conflict. However, in addition to enriching the description of relational mediation practices, theories of intersubjectivity also offer an analysis that includes dimensions of conflict that may prove to be resistant to developing new intersubjective understanding between parties in conflict and thus, may resist resolution when certain approaches are used. This thesis employs a three-part structure. The first part of this thesis lays the foundation for the development of the argument, namely that conflict is experienced through the lens of subjectivity and that relational mediation tends to work in this realm. Working under the assumption that conflict is created in the subjective experiences of parties, mediation presumes that addressing conflict through the subjective experiences of the parties offers a suitable path to resolution. Furthermore, this thesis offers a review of how the conflict studies field views success in mediation and the various mediation models developed in various contexts and narrows the field of inquiry to a particular mediation approach, the relational mediation approach. The relational mediation approach, consisting of a series of mediation models, describes an approach to conflict resolution that presumes that while people are concerned with their own interests, they also are simultaneously concerned with the interests of others. This mutual-concern approach stands in contrast to individualist interpretations of conflict resolution as a problem-solving approach that prioritizes having one's own needs met with minimal concern for the interests of the other party. In this thesis, the scope for examination is narrowed to the transformative, insight, narrative, and nonviolent communication models of mediation as they share the relational orientation to their respective theories and practices. Having narrowed and clearly defined the goals of relational mediation models, the second part of this thesis situates relational mediation practices within the phenomenological approach to conflict resolution. This approach explores conflict through the lens of first-person experience using methods familiar to phenomenologists. Using a phenomenological approach, relational mediators seek to guide mutual understanding between parties about how the conflict has presented itself to each party. Thus, this thesis further contends that relational mediators are unknowingly working with theories of intersubjectivity to guide parties toward new shared understandings of self, other, and the conflict as they promote mutual cognitive and empathic understanding. Indeed, the mediator is equally participatory in this intersubjective understanding as it is often considered as an integral part of the mediation process. Having established that relational mediation models employ their own version of theories of intersubjectivity, the final part of this thesis uses literature from theories of intersubjectivity to discern likely blocks to intersubjective understanding. With the definition of these blocks established through the lens of intersubjectivity, this thesis contends that some conflicts are inherently resistant to resolution through mediation because of individual dispositions or structural influences on the parties and their conflicts. This thesis contends that applying the lens of theories of intersubjectivity to relational mediation theories and practices provides new paths in mediation’s theoretical and practical maturation and adds to the tools mediators may already be applying. Specifically, theories of intersubjectivity shed light on the quality of dynamics mediators seek to prompt during a mediation process. However, theories of intersubjectivity also point toward explanations about party dispositions and contexts that are likely to contribute to mediation failure. Exploring these dimensions of relational mediation approaches offers paths for mediator development to help them address these challenges in mediation or to help to guide them in determining whether a conflict should be referred to another dispute resolution mechanism.
Keywords: Mediation; Intersubjectivity; Conflict resolution